2020
DOI: 10.1186/s12891-020-03621-7
|View full text |Cite
|
Sign up to set email alerts
|

Defining pain and interference recovery trajectories after acute non-catastrophic musculoskeletal trauma through growth mixture modeling

Abstract: Background Recovery trajectories support early identification of delayed recovery and can inform personalized management or phenotyping of risk profiles in patients. The objective of this study was to investigate the trajectories in pain severity and functional interference following non-catastrophic musculoskeletal (MSK) trauma in an international, mixed injury sample. Methods A prospective longitudinal cohort (n = 241) was formed from patients identified within four weeks of trauma, from attendance at emer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…Data were drawn from a prospective observational study of recovery following acute non-catastrophic MSK injury (the ‘Systematic Merging of Biology, Mental Health and Environment’ (SYMBIOME) study, clinicaltrials.gov ID number NCT02711085). Methods of screening and recruitment have been described previously [ 39 ]. In short, eligible participants were at least 18 years or older, presented to a local urgent care centre for reasons of pain or functional interference following MSK trauma within the prior 3 weeks, did not require inpatient admission or surgery, could read and understand conversational French or English, and did not have a systemic or chronic condition that would be expected to delay recovery such as cancer, neuromuscular disorders or other significant systemic diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Data were drawn from a prospective observational study of recovery following acute non-catastrophic MSK injury (the ‘Systematic Merging of Biology, Mental Health and Environment’ (SYMBIOME) study, clinicaltrials.gov ID number NCT02711085). Methods of screening and recruitment have been described previously [ 39 ]. In short, eligible participants were at least 18 years or older, presented to a local urgent care centre for reasons of pain or functional interference following MSK trauma within the prior 3 weeks, did not require inpatient admission or surgery, could read and understand conversational French or English, and did not have a systemic or chronic condition that would be expected to delay recovery such as cancer, neuromuscular disorders or other significant systemic diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Recovery of posttrauma pain can therefore be summarized as very slow and by no means certain for all, a message consistent with previous studies. 5 , 6 , 7 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…After LPA, each participant was assigned to one of the identified classes based on relative blood marker concentration. From a previous study 12 of derivation of recovery curves, each participant was also assigned to one of three trajectory classes: rapid, delayed, or minimal recovery. Both the rapid and delayed recovery groups were grouped together as a “recovery predicted” group and proportions of the blood marker clusters were statistically compared against the “minimal or no recovery predicted” group using chi-square analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal modeling studies in both clinical (6) and population-level (7) samples have identified trajectories of pain and recovery that most commonly indicate 15-25% of participants report long-term, chronic or persistent pain and functional interference after musculoskeletal trauma seemingly regardless of the body region affected (6,(8)(9)(10)(11). In a prior study (12) we identified a 3-trajectory model of functional recovery from musculoskeletal (MSK) trauma representing trajectories of rapid recovery (32.0% of the sample), delayed recovery (26.7%), and minimal or no recovery (41.3%). To briefly summarize, these trajectories were based on disability due to pain (or "pain interference") over the course of 12 months where rapid recovery had the lowest symptoms at baseline with near or full recovery by 3 months, delayed recovery had high symptoms at baseline with full recovery by 12 months, and minimal/no recovery had high symptoms at baseline that persisted throughout the study.…”
Section: Introductionmentioning
confidence: 99%